Bioactive Molecules and Medicinal Plants - Ramawat, Kishan Gopal (Springer, 2017)
Drug Discovery from Plants -- Grapevine Stilbenes and Their Biological Effects -- Research into Isoflavonoid Phyto-oestrogens in Plant Cell Cultures...